Gastric Pneumatosis in a Premature Neonate - Ting, Yuk Joseph; Chan, Kwong-leung; Wong, Siu-chun Mabel; Chim, Stella; Wong, Kar-yin (American Journal of Perinatology Reports, 2011)
Gastric pneumatosis is extremely rare during infancy. It has been reported in association with necrotizing enterocolitis or congenital abnormalities such as pyloric stenosis. Here, we report a case of gastric pneumatosis in a premature neonate on synchronized nasal intermittent positive pressure ventilation. No pneumatosis was noted in the rest of the bowel or esophagus. There could have been mild damage in the gastric mucosa, either related to the placement of the feeding tube or secondary to the use of indomethacin or both. The condition was further aggravated by noninvasive ventilation. An increase in intragastric pressure resulted in the submucosal dissection of air followed by the development of gastric pneumatosis. Conservative management strategies, including the use of a nasogastric tube for decompression and the withholding of feeding, successfully managed the gastric pneumatosis in our patient. An uneventful recovery was made after conservative management. Prompt recognition and evaluation of this condition were essential for making the diagnosis.
Keywords: Gastric pneumatosis; preterm; neonate; synchronized nasal intermittent positive pressure ventilation